NARKOBA: BAHAYA PENYALAHGUNAAN DAN PENCEGAHANNYA - Nur S Gono, Joyo (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :Narcotic abuse over children should get more attention and concern from all instrument of society including family, social institution and government. So far, the network of narcotic market driven by a latent syndicate that has consumer target 14 to 18 years old children who still have an unstable attitude. This condition might hazard Indonesian youth because they are the next generation who will develop this country in the future. So, this is an urgent step to prevent the drug consumption among children and destroy its syndicate in order to save and secure this nation. This paper provide description about the danger of drug and how to prevent children not to consume it.Keywords : Narcotic abuse, Socializationpermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3162